Comparison of anthropometric and performance characteristics in elite male football and handball players - Karadenizli, Z. I.; Ilbak, I.; Bartik, P. (Journal of Human Sport & Exercise, 2026)
Elite-level athletes develop distinct performance profiles shaped by training regimens tailored to the specific physical and physiological demands of their respective sports. The nature of the sport, training methods, and game dynamics directly influence the development of strength, power, speed, and anthropometric characteristics. In team sports, comparative evaluations of these attributes are critical for accurate performance analysis and the design of sport-specific and individualized training pro-grams. This study aimed to compare the anthropometric characteristics, strength, ex-plosive power, and speed parameters of elite male football and handball players. A total of 44 athletes (22 football players and 22 handball players) participated in this cross-sectional comparative study. Anthropometric data included height (cm), body weight (kg), and body mass index (BMI, kg/m²). Performance assessments comprised leg strength (kg), handgrip strength (kg), vertical jump height (cm), 30-meter sprint time (s), and peak power output (W). Independent samples t-tests revealed statistically significant differences between football and handball players in age (p = .004), height (p = .005), leg strength (p = .007), and handgrip strength (p < .001). No significant differences were found in other performance variables (p > .05). The findings indicate that elite football and handball players exhibit sport-specific anthropometric and performance profiles. Football players showed greater lower-body strength, while hand-ball players had superior upper-body strength and greater stature. These differences underscore the importance of developing training protocols and talent identification strategies that reflect the unique demands of each sport. Coaches are encouraged to utilize sport-relevant performance tests and interpret results contextually to optimize athlete development and specialization.